2014
DOI: 10.1007/s00330-014-3330-7
|View full text |Cite
|
Sign up to set email alerts
|

3D FIESTA pulse sequence for assessing renal artery stenosis: is it a reliable application in unenhanced magnetic resonance angiography?

Abstract: The 3D FIESTA sequence provides a robust evaluation of RAS. The 3D FIESTA sequence allows non-invasive evaluation of the renal arteries. The 3D FIESTA sequence could be a useful tool in evaluating RAS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…5,6 MRA of the renal arteries may be performed with or without the use of gadolinium-based contrast agents (GBCAs). Although new techniques for performing unenhanced MRA of the renal arteries are under investigation, particularly the use of balanced steady-state free-precession MRA, [7][8][9] unenhanced MRA of the renal arteries has historically been performed using a 2D time-of-flight (ToF) technique, which can detect very slow flow. Contrast-enhanced (CE)-MRA improves structural delineation of vessel segments, thereby improving the overall performance of the MRI.…”
mentioning
confidence: 99%
“…5,6 MRA of the renal arteries may be performed with or without the use of gadolinium-based contrast agents (GBCAs). Although new techniques for performing unenhanced MRA of the renal arteries are under investigation, particularly the use of balanced steady-state free-precession MRA, [7][8][9] unenhanced MRA of the renal arteries has historically been performed using a 2D time-of-flight (ToF) technique, which can detect very slow flow. Contrast-enhanced (CE)-MRA improves structural delineation of vessel segments, thereby improving the overall performance of the MRI.…”
mentioning
confidence: 99%
“…Recent studies have shown comparable results between U-MRA and CE-MRA, CTA and DSA in both healthy volunteers and patients with renal artery stenosis. These studies are summarized in Table 4 [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] ( Fig. 2 , Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In the two cases, there were multiple areas of stenosis and dilatations in the main renal arteries, making correct evaluation of renal arteries more challenging even for the gold standard techniques. There are only two articles available where FMD is depicted using U-MRA [23] , [24] , [25] ( Fig. 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…The assessment of the renal arteries was carried out as reported in a previous study. 19 In their analysis, the readers noted the number of renal arteries on both sides; the arteries entering the renal hilum were considered as the main renal arteries. The presence or absence of accessory renal arteries were also assessed, and the same evaluation regarding the possible presence of stenosis was attempted.…”
Section: Image Analysismentioning
confidence: 99%